Pengaruh Keselamatan dan Kesehatan Kerja serta Beban Kerja terhadap Kinerja Pekerja Proyek Konstruksi - Djaelani, Mohammad; Darmawan, Didit (Pusat Riset dan Inovasi Nasional, 2022)
The performance of workers is one part of being able to develop a business. Not only demanding from the side of workers, companies also need to pay attention to work facilities to improve worker performance. Occupational Health and Safety is one part of the labor law. Every employer organization is required to implement Occupational Health and Safety in the implementation of work. Occupational Health and Safety is an important element to build worker performance. In addition, the perceived workload will determine the performance of workers. This study aims to determine the role of Occupational Health and Safety and workload on the performance of construction workers. This study uses 89 respondents who are construction workers. Data were obtained using a questionnaire which was distributed to the research sample. This study uses regression analysis. The results showed that Occupational Health and Safety had a significant influence on the formation of worker performance. Furthermore, the performance of workers is also known to be significantly influenced by workload. The two variables, namely Occupational Health and Safety and workload, are known to have a significant influence together on the formation of worker performance.